ANALISIS KAUSALITAS KETERAMPILAN PIMPINAN DAN MORAL KERJA TERHADAP KEDISIPLINAN PEGAWAI PEMERINTAHAN - Rosyidah Rachman; Husni Husni (Fakultas Ekonomi dan Manajemen, 2023)
This study aims to know the effect of leadership skills and work morale on the discipline of government employees. This research was conducted at the Rhee Village Office, Rhee Sub District, Sumbawa District. This type of research is associative research. The type of data used is quantitative data obtained directly from primary sources collected through questionnaires. The population in this study were all employees at the Rhee Village Office, Rhee Sub District, Sumbawa District, totaling 17 people. Taking into account the relatively small number of members of the population, all members of the population are sampled or use a census sampling technique. Data analysis was performed using multiple linear regression analysis techniques, partial parameter hypothesis testing (t test), simultaneous parameter hypothesis testing (F test), and determinant coefficient test (R2). The results of this study indicate that the leadership skills and work morale have a positive and significant effect on the discipline of government employees at the Rhee Village Office, Rhee Sub District, Sumbawa District, either partially or simultaneously. The degree effect of leadership skills and work morale on employee discipline in the Rhee Village Office, Rhee Sub District, Sumbawa District is 88.9%, while the remaining of 11.1% was affected by other variables outside of this study, such as employee competence, remuneration (salary and welfare), inherent supervision, and sanctions/penalties.